2002
DOI: 10.2165/00002018-200225110-00003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Tolerability of the Bisphosphonates in Postmenopausal Osteoporosis

Abstract: Osteoporosis in postmenopausal women is a growing health concern for society. Bisphosphonates have become the mainstay of prevention and treatment with the mounting evidence of their efficacy over the past two decades. This review article examines the use of the etidronate, alendronate and risedronate. The pivotal trials are reviewed for long-term tolerability, evidence regarding histological safety and gastrointestinal tolerance. Etidronate, alendronate and risedronate have also been examined in meta-analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The results raise interesting questions regarding management of potential gastrointestinal events associated with bisphosphonate use and the implications for healthcare costs. While adverse oesophageal events associated with bisphosphonate use are well known, it is suggested from the randomized controlled studies that this can be minimized [4–6]. Further research is required to determine if the observed increase in utilization of acid suppressing medicines found in this study is related to lack of adherence to administration protocols and whether this is related to the adequacy of instructions, education and follow‐up to consumers regarding appropriate administration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results raise interesting questions regarding management of potential gastrointestinal events associated with bisphosphonate use and the implications for healthcare costs. While adverse oesophageal events associated with bisphosphonate use are well known, it is suggested from the randomized controlled studies that this can be minimized [4–6]. Further research is required to determine if the observed increase in utilization of acid suppressing medicines found in this study is related to lack of adherence to administration protocols and whether this is related to the adequacy of instructions, education and follow‐up to consumers regarding appropriate administration.…”
Section: Discussionmentioning
confidence: 93%
“…Reports of oesophagitis, oesophageal ulceration or oesophageal stricture associated with bisphosphonate use have been commonly reported via spontaneous adverse drug reaction reporting mechanisms [1, 2] and via prescription event monitoring studies [3]. Reviews of the clinical trial results suggest the incidence of upper adverse gastrointestinal events associated with bisphosphonate use are not significantly greater than placebo [4–6], suggesting this adverse event can be minimized. In an environment where there is potential for extensive use of bisphosphonates, with estimates that as many as 30% of postmenopausal women may require treatment and even greater potential for use if these medicines were used for primary prevention of osteoporosis, it becomes important, where possible, to minimize the occurrence of this adverse drug event.…”
Section: Introductionmentioning
confidence: 99%
“…However, bisphosphonate treatment is not without risk and serious adverse drug reactions (ADRs), including osteonecrosis of the jaw [5], oral and gastric carcinomas [6-8], atypical femur fractures [9,10], and upper gastrointestinal bleeding (UGIB), although infrequent, have been described but remain controversial [11-15]. Drug induced dysphagia, esophagitis, and gastric ulcers are the most common of the gastrointestinal (GI) ADRs associated with oral bisphosphonate therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative review of pivotal trials of alendronic acid and risedronic acid including a meta-analysis, Kherani et al 114 concluded that both alendronic acid and risedronic acid result in similar rates of AEs as placebo.…”
Section: Systematic Review Evidence For Adverse Eventsmentioning
confidence: 99%